ChemInform Abstract: Magnetic Properties of MM′X (M = Mn, M′ = 3d or 4d Metal, X = P, As, Si, Ge) Compounds with Hexagonal or Orthorhombic Crystal Structure. Issue 4 (28th January 2014) - Zach, Ryszard; Tobola, Janusz; Chajec, Wieslaw; Fruchart, Daniel; Ono, Fumihisa
Abstract Review: 16 refs.